Synthesis and properties of pteridine-2, 4-dione-functionalised oligothiophenes. Issue 10 (19th January 2016) - Wiles, Alan A.; Fitzpatrick, Brian; McDonald, Niall A.; Westwater, Mary Margaret; Long, De-Liang; Ebenhoch, Bernd; Rotello, Vincent M.; Samuel, Ifor D. W.; Cooke, Graeme
Abstract : The synthesis of symmetrical acceptor-functionalised oligothiophenes is described and their electrochemical and optical properties are reported. Abstract : The synthesis of acceptor-functionalised oligothiophene derivatives (t3, t6, t7, t8 ) is described, where the pteridine-2, 4-dione acceptor units are arranged symmetrically in derivativest6–t8 . The symmetrical arrangement of acceptor units stems from the ability to selectively brominate the conjugated thiophene moiety of building blockt3 . Upon increasing the conjugation by going fromt3 tot8, a significant increase in absorption toward the near-infrared region and a simultaneous narrowing of the HOMO/LUMO gap occurs, which may promote their future application as optoelectronic materials.